Loading of CAR‐T cells with magnetic nanoparticles for controlled targeting suppresses inflammatory cytokine release and switches tumor cell death mechanism - Felix Pfister; Lucas R. Carnell; Lisa Löffler; Philipp Boosz; Niels Schaft; Jan Dörrie; René Stein; Malte Lenz; Erdmann Spiecker; Christian M. Huber; Sami Haddadin; Carola Berking; et al. (MedComm)
Abstract Therapies against hematological malignancies using chimeric antigen receptors (CAR)‐T cells have shown great potential; however, therapeutic success in solid tumors has been constrained due to limited tumor trafficking and infiltration, as well as the scarcity of cancer‐specific solid tumor antigens. Therefore, the enrichment of tumor‐antigen specific CAR‐T cells in the desired region is critical for improving therapy efficacy and reducing systemic on‐target/off‐tumor side effects. Here, we functionalized human CAR‐T cells with superparamagnetic iron oxide nanoparticles (SPIONs), making them magnetically controllable for site‐directed targeting. SPION‐loaded CAR‐T cells maintained their specific cytolytic capacity against melanoma cells expressing the CAR‐specific antigen chondroitin sulfate proteoglycan (CSPG4). Importantly, SPIONs suppressed cytokine release in the loaded CAR‐T cells, shifting the cell death phenotype in the tumor cells from pyroptosis to apoptosis. Furthermore, SPION‐loaded CAR‐T cells could be enriched in a dynamic flow model through an external magnetic field and be detected in MRI. These results demonstrate that lytic cytotoxicity is retained after SPION‐functionalization and provides a basis for future site‐specific immunotherapies against solid tumors with reduced systemic adverse side effects.